Punching the clown [videorecording (DVD)] - Viens, Gregori; Phillips, Henry, 1969-; Ratner, Ellen, 1951-; Kelley, Wade; Walker, Matt; Siegel, Audrey (Viens Films, 2009)
"When a talented but hapless traveling songwriter (Henry Phillips) moves to LA to shake things up, his luck changes overnight. Thanks less to his inept manager than to a wild case of mistaken identity, he falls backwards into a string of packed gigs, a record deal and even the promise of love. But he who lives by the whimsy of show business dies by it: an innocent miscommunication over a bagel makes him the victim of a vicious rumor in the tabloids. Luckily, somewhere between rock bottom and the middle of nowhere lies the perfect terrain for Henry's dark and hilarious songs"--Container.